2021
DOI: 10.3390/biomedicines9010032
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cell Death Induced by Ca2+ Delivery via Microbubble Cavitation

Abstract: Intracellular calcium ion delivery via sonoporation has been validated to be a substitute for classical chemotherapy. However, the mechanism behind calcium sonoporation remains unclear to this day. To elucidate the role of calcium in the process of sonoporation, we aimed to investigate the influence of different calcium concentration on cell membrane permeabilization and cell viability after sonoporation. In this study, we present experimental evidence that extracellular calcium plays a major role in cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, it has been demonstrated that increasing activation firings and duty cycles induce cell death during the sonoporation process 39–41 . Continuous inertial cavitations have also been reported to induce the production of reactive oxygen species or suddenly evoke calcium influx to cause cell death 29,32 . Accordingly, the optical and acoustic parameters need to be carefully selected to achieve effective sonoporation while minimizing cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been demonstrated that increasing activation firings and duty cycles induce cell death during the sonoporation process 39–41 . Continuous inertial cavitations have also been reported to induce the production of reactive oxygen species or suddenly evoke calcium influx to cause cell death 29,32 . Accordingly, the optical and acoustic parameters need to be carefully selected to achieve effective sonoporation while minimizing cell death.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Continuous inertial cavitations have also been reported to induce the production of reactive oxygen species or suddenly evoke calcium influx to cause cell death. 29,32 Accordingly, the optical and acoustic parameters need to be carefully selected to achieve effective sonoporation while minimizing cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium ion delivery, enhanced by different intracellular delivery modalities, such as electroporation (EP) [ 14 , 15 ] and SP [ 16 ], has been proposed as a favorable alternative to regular chemotherapy. A plethora of extracellular stimuli are able to implicitly increase the intracellular level of diffusible Ca 2+ , which, in turn, acts as a second messenger and controls a milieu of intrinsic cellular processes, including the mechanism of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in comparison to traditional chemotherapy, the employment of US-MB-mediated delivery of supra-physiological Ca 2+ levels for cancer treatment can significantly diminish the serious after-effects inflicted by conventional cytotoxic drugs, particularly following intravascular or oral administration. However, Ca 2+ delivery and possible therapeutic applications are poorly investigated in the field of SP, except for our previous work [ 16 ]. Therefore, in the first part of our research, we aimed to determine the possible Ca 2+ applications for chemotherapy by comparing the levels of cell death induced in Chinese hamster ovary (CHO) cells by both Ca 2+ and BLM after SP.…”
Section: Introductionmentioning
confidence: 99%